Sophorolipids Production from Oil Cake by Solid-State Fermentation. Inventory for Economic and Environmental Assessment - Rodríguez, Alejandra; Gea, Teresa; Font, Xavier (Frontiers in Chemical Engineering, 2021)
Biosurfactants are being pointed as a substitute for surfactants in the framework of a circular economy strategy. Sophorolipids (SL) are a type of biosurfactant produced by yeast that can be produced through submerged or solid-state fermentation (SSF) processes. Even that sophorolipids are being produced at full scale through submerged fermentations, environmental and technoeconomic information regarding its production through SSF is unavailable. An inventory of data necessary to perform preliminary economic and environmental assessments is presented in this study. Data is obtained from three SSF processes at 22-L reactor volume and from two SSF processes at 100-L reactor volume, using winterization oil cake and molasses as substrates, wheat straw as support material and Starmerella bombicola as SL producing yeast. The effect of increasing operation scale is assessed. Besides presenting parameters such as inoculum production, initial mass of substrates and airflow requirements; process emissions (NH3, Volatile Organic Compounds, N2O, SH2 and CH4) and the biogas potential of the spent fermentation solids are also presented.